Repolarisation and refractoriness during early ischaemia in humans. Issue 4 (1st October 2000) - Sutton, P M I; Taggart, P; Opthof, T; Coronel, R; Trimlett, R; Pugsley, W; Kallis, P
Abstract : OBJECTIVES: To determine whether effective refractory period (ERP) shortens or lengthens in the first minutes of ischaemia in humans, and the relation between ERP changes and action potential duration (APD). METHODS: ERP and monophasic action potential duration (MAPD) were measured from a single left ventricular epicardial site in 26 patients undergoing coronary artery surgery. Cardiopulmonary bypass was instituted and normothermia maintained. Refractory period was determined by the extrastimulus technique at a basic cycle length of 500 ms, at four times (group 1, 15 patients) or two times (group 2, 11 patients) the preischaemic diastolic threshold. A three minute period of ischaemia was instituted by aortic cross clamping between the input from the pump oxygenator and the heart. RESULTS: After three minutes of ischaemia, mean (SEM) ERP lengthened from 232 (5) ms (control) to 246 (7) ms (p < 0.005) in group 1, and from 256 (10) ms (control) to 348 (25) ms (p < 0.005) in group 2. In the same time MAPD shortened from 256 (5) ms (control) to 189 (9) ms (p < 0.001) with no difference between groups. Thus postrepolarisation refractoriness developed during ischaemia. Before ischaemia, ERP showed a good correlation with APD ( R 2  = 0.64) but by one minute of ischaemia the correlation was poor ( R 2  = 0.29). CONCLUSIONS: These results show that during the first three minutes of global ischaemia in patients with coronary artery disease: (1) ERP lengthened in response to both a low and a high stimulus strength; and (2) there was a good correlation between ERP and APD before ischaemia, which was lost by one minute as APD decreased and ERP increased. These findings may have important implications in arrhythmogenesis.